The slavery businnes - Olusoga, David; Miles, Rupert; Richards, Chris (United Kingdom : The open University Worldwide, 2005)
This two-part docu-drama charts the dynamic rise of a dynasty based on slavery ; its dramatic fall, and how the slaves eventually won their freedom
Breaking the chains (59 min.) -- Sugar dynasty (58 min.)
Title from title screen
Editore, Peter Simpson, Stuart Barlow ; sound, Bill Rudolf ; camera, Robin Cox
Narrator: Anthony Howell
DVD Format
Keywords: Slavery -- Great Britain; Forced labor